Multidisciplinary Approach to the Management of a Patient with Right-Sided Infective Endocarditis on Maintenance Hemodialysis - E. Yu. Ponomareva; N. A. Kosheleva; D. S. Sedov (Архивъ внутренней медицины)
Infective endocarditis in patients on maintenance hemodialysis occurs more often than in the population, manifests severe complications and is characterized by high mortality. The management of such patients requires the participation of several specialists. In the presented clinical observation, both typical characteristics of infective endocarditis on maintenance hemodialysis (staphylococcal etiology, association with vascular access devices, metabolic and hemodynamic risk factors) and peculiarities of a particular case (nature of nephropathy that led to maintenance hemodialysis, mechanism of right heart damage, which is uncommon for infective endocarditis on maintenance hemodialysis) are discussed in comparison with literature data. Interdisciplinary interaction of doctors of several specialties contributed to the choice of the right tactics and a favorable outcome of the disease.